Hubungan Bahan Organik Total (BOT) Sedimen dengan Struktur Vegetasi Mangrove di Desa Bonto Bahari Kecamatan Bontoa Kabupaten Maros - Isman, Muh; Irwan Achmad, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Mangrove forests are a distinctive type of forest found along the coast or river estuaries. This research was conducted in October 2023 on the coast of Bonto Bahari Village, Bontoa District, Maros Regency, South Sulawesi Province. Data collection includes preparation of tools and materials to be used at the research site. Data collection of mangrove ecosystems using line transects along 100 meters then draw transect lines perpendicular to the shoreline. Furthermore, placing a quadrant plot measuring 10 meters x 10 meters at three observation stations and three repetitions of each station. To determine the category of mangrove conditions based on the Minister of Environment Decree No. 201 of 2004, the identification of mangrove species using mangrove introduction guidebook. The measurement of environmental conditions directly measured at the study site includes parameters of temperature, salinity, soil pH taken at each observation station, as well as taking sediment at each station for the measurement of Total Organic Matter (BOT) tested in the laboratory, BOT analysis was performed using the method of burning with high temperature (550oC) (loss on ignition) for 2 hours. Based on the results of the study found 4 types of mangroves namely Avicennia alba, Avicennia marina, Rhizophora mucronata, and Rhizophora apiculata. Avicennia alba mangrove has the highest density value compared to other mangrove species. The substrate found at each station is medium sediment (medium sand). The results of PCA analysis showed that mangroves in the study site were influenced by salinity, temperature, and sediment pH. Mangrove density is more influenced by the total organic matter (BOT) content of sediments.